THE EXTENT OF THE STUDY OF WORD-FORMATION AND AFFIXATION BY CHINESE LINGUISTS - Mukhamedova, Odinakhon Makhamadaliyevna (Innovative Development in Educational Activities, 2023)
The need for language teaching and learning is ever increasing in today’s idealize and creating countries. There’s moreover a developing interest in learning foreign languages in Uzbekistan, as well as the life, culture and history of these languages. Words develop in accordance with the language development laws. However, they are not the same in all languages. Accordingly, it is important to memorize such tools on the basis of the rules of each language. On this basis, our investigate work looked for to cover the issue of word formation using the affixation method, which could be a morphological method in Chinese and Indonesian.